Indicator environmental variables in regulating the distribution patterns of small freshwater fish Amblypharyngodon mola in India and Bangladesh. (January 2021) - Roy, Sangeeta; Ray, Santanu; Saikia, Surjya Kumar
Highlights: Ensemble species distribution modelling was done for freshwater fish. Occurrence records of small freshwater fish Amblypharyngodon mola were used. Climatic, topographic, landcover and soil variables were used as predictors. Upstream precipitation, soil pH and elevation were found to be the key indicators. Ganges delta region was found to be most suitable habitat. Abstract: The key challenge in the fields of conservation and resource management is to track local, regional and global species extinctions and preserve biodiversity through optimization of investment of funds. To fulfil that purpose modelling and mapping habitat suitability of species is becoming essential. The freshwater ecosystem is today one of the most threatened ecosystems and fishes are especially vulnerable for climate change as they have fewer choices for dispersal. The altered thermal regimes, land use and hydrology together cause isolation, fragmentation and changes in distributional patterns of fish. In such landlocked situation, there is utmost need to identify suitable environmental conditions for a species to exist. Indigenous fish is one of the essential components of healthy inland aquatic ecosystems as they fulfil several important ecological functions and form an important part of the aquatic food web. Amblypharyngodon mola is an economically and ecologically important indigenous freshwater fish species of the tropical and subtropical floodplain rivers and wetland habitats of India and Bangladesh. However, lack of knowledge about the key environmental indicators is hindering appropriate management and conservation initiation. Modelling and mapping the distribution of A. mola was done for identifying the key environmental variables and predicting the potential distribution area of the species in current climatic condition. The species occurrence data were accessed from both primary and secondary sources and used after cleaning and removing biasness. Climatic, topographic, landcover and soil variables of 1 km resolution were used as environmental predictors. India and Bangladesh together were used as model background. Ensemble species distribution modelling was done, and the model was validated by area under the curve (AUC) value (>0.7). The result showed that the Ganges delta of lower reach going through West Bengal and Bangladesh is most suitable for A. mola occurrence. Annual upstream precipitation (hydroclim_12), soil pH in water (soil_average_02) and elevation (ele_01) are the key indicators for predicting the habitats suggesting the importance of hydroclimatic, topographic and soil variables in determining the distribution of the fish.